Resilience and Its Association with Depression, Emotional and Behavioural Problems, and Mental Health Service Utilisation among Refugee Adolescents Living in South Australia. (20th June 2012) - Ziaian, Tahereh; de Anstiss, Helena; Antoniou, Georgia; Baghurst, Peter; Sawyer, Michael
Abstract : Background . Despite the frequency of traumatic or stressful events experienced by refugee children and adolescents prior to migration and following resettlement, the majority do not experience mental health problems emphasising the critical nature of resilience. While a host of factors deemed to be protective of mental health in young refugees have been identified, there has been little research exploring the role of resilience as a distinct psychological construct. This study aimed to explore the nature of psychological resilience in refugee adolescents and the relationship between resilience and depression, other emotional and behavioural problems, and mental health service uptake. Method . One hundred and seventy multiethnic refugee adolescents aged 13–17 from South Australia were administered a survey comprising the Connor-Davidson Resilience Scale (CD-RISC), Children's Depression Inventory (CDI), and Strengths and Difficulties Questionnaire (SDQ). Results . Females tended to have higher resilience, as did those adolescents who had been living in Australia longer. Adolescents suffering from depressive symptoms or other emotional or behavioural problems had lower resilience. There was little evidence of an association between resilience scores and exposure to trauma or service utilisation. Discussion . Fostering resilience may be critical to efforts to prevent or reduce mental health problems in refugee adolescents.